The relationship between supply chain risk, flexibility and performance in the South African public sector. - Mhelembe, K. (My University, 2018)
The expectation by South Africans is that the public sector must contribute positively to the economy. However, the general perception is that the public sector is failing to fulfil its mandate due to systemic problems in the entire public sector. Its supply chain in South Africa is both volatile and imperfect. This is demonstrated by the level of service delivery protests, which emanate from the feeling that the public is not receiving the quantity or quality service that they need. This study aimed to assess the relationship between supply chain risks, supply chain flexibility and supply chain performance in the South African public sector. A conceptual framework was developed, which included six supply chain risk factors, namely, government policies, supply complexity, availability of skills, supplier performance monitoring, information security and process efficiency, which feed into supply chain flexibility, which in turn leads to supply chain performance. Seven hypotheses underlying these relationships were put forward for testing. A quantitative approach using the cross-sectional survey design was adopted in which a questionnaire was distributed to 306 conveniently selected supply chain professionals who were based in Gauteng province. Items used in the survey questionnaire were adapted from previously validated scales. A confirmatory factor analysis was conducted to test the psychometric properties of the measurement instrument. Descriptive statistics were used to analyse the perceptions of respondents towards the factors under consideration in the study. Hypotheses were tested using the structural equation modelling approach. The results of the study show that the threat from supply chain risks in the South African public sector remains high, and that flexibility and performance of the supply chain remains unsatisfactory. Hypotheses tests showed that all six supply chain risks significantly predicted supply chain performance. While the other supply chain risks were positively related to supply chain flexibility, the relationship between the flexibility and supply complexity was negative. Amongst the supply chain risks considered in this study, availability of skills emerged as the strongest predictor of supply chain flexibility. The study further showed that supply chain flexibility significantly and positively predicts supply chain performance. Theoretically, the study provides a specific conceptualization of the relationship between supply chain risks, supply chain flexibility and supply chain performance within the South African public sector, where no such study has been conducted before. Practically, it provides information to supply chain professionals in the South African public sector regarding the improvement of supply chain performance. The study underscores that the performance public supply chain in South Africa can be improved by managing the six risks considered in this study, and their contribution to supply chain flexibility.
D. Tech (Department of Human Resource Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: public sector, economy, service delivery, supply chain risks; Risk management -- South Africa.; Performance management -- South Africa.; Civil service -- South Africa.